ANALISIS NOVEL LAYAR TERKEMBANG KARYA ST. TAKDIR ALISJAHBANA DALAM PENDEKATAN PSIKOLOGI KEPRIBADIAN - Elan Halid (eScience Humanity Journal, 2022)
The problem to be discussed in this research is how the analysis of the novel Layar Terkembang by St. Alisjahbana's destiny in personality psychology approaches. Novels are works of fiction that reveal deeper aspects of humanity and are presented in a subtle way. Novel is defined as giving a firmer concentration of life, with romance which is defined as a broader design. Personality psychology is a branch of psychology that discusses and studies the nature and character of individuals as a unique personality that differs from one individual to another. The reason the researcher conducts research on the novel Layar Terkembang is because it tells the struggle of Indonesian women in terms of the id, ego, and superego. In this novel there is a psychological approach to the author's psychology and the content of the story in the novel, so that the reader feels more immersed in the novel Layar Terkembang. The purpose of this study is to describe the analysis of the novel Layar Terkembang by St. Alisjahbana's destiny in personality psychology approach. This type of research is a qualitative research using descriptive method. The data of this research are the quotations in the novel Layar Terkembang. In this study, the data source used by the researcher was the novel Layar Terkembang. From the research data findings, the researcher found 19 data. The psychology of literature on the personality of the character is about the id, there are 6 data, the ego has 7 data, and the superego has 6 data. The conclusion of the research on the literary psychology of the character's personality from all the characters in the main character and additional characters shows that the personality of the "ego" character is the most dominant.